Comprehensive Evaluation of Vertical Sub-Surface Flow Constructed Wetlands with Aquatic Plants on Water Quality of Raw and Phyto-Remediated Poultry-Aquaculture Wastewater: A Principal Component Analysis - Akadiri, Shadrach A.; Dada, Pius O.O.; Badejo, Adekunle A.; Adeosun, Olayemi J.; Faloye, Oluwaseun T.; Adeyeri, Oluwafemi E.; Laokhongthavorn, Laemthong; Kamchoom, Viroon (My University, 2026)
This study investigated the efficiency of macrophyte-based phytoremediation systems using Phragmites karka and Typha latifolia for the treatment of poultry–aquaculture wastewater and its suitability for irrigation reuse. Physicochemical parameters, heavy metals, and water quality indices were analysed using correlation analysis and Principal Component Analysis (PCA). Strong positive correlations were observed among turbidity, nutrients, biochemical oxygen demand (BOD5), and chemical oxygen demand (COD), while dissolved oxygen (DO) showed significant negative relationships, indicating organic pollution-driven oxygen depletion. Heavy metals exhibited strong intercorrelations, suggesting common anthropogenic sources and similar removal pathways. PCA results revealed that the first three principal components (PCs) explained over 95% of the total variance, with positive values recorded from the first PC highlighting organic load, nutrient enrichment, and metal interactions as dominant factors controlling wastewater quality. The negative values of factor loadings obtained in the second and third PCs confirmed the roles of sedimentation, adsorption, microbial activity, and plant uptake in pollutant removal. Water Quality Index (WQI) values decreased drastically from highly polluted levels (>3000) in raw wastewater to <1.0 after 21 days of treatment, indicating excellent water quality. Sodium Absorption Ratio (SAR) also declined significantly, confirming a low sodicity risk. Both macrophytes demonstrated high treatment efficiency, with Typha latifolia showing slightly improved sodium reduction. Overall, the study highlights macrophyte-based systems as sustainable, cost-effective solutions for wastewater treatment and safe agricultural reuse.
Keywords: constructed wetland; heavy metals removal; phytoremediation; poultry-aquaculture wastewater; water quality index